2019
DOI: 10.1128/jvi.00352-19
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Marek's Disease Virus Is Dependent on Synthesis of De Novo Fatty Acid and Prostaglandin E 2

Abstract: Marek’s disease virus (MDV) causes deadly lymphoma and induces an imbalance of the lipid metabolism in infected chickens. Here, we discovered that MDV activates the fatty acid synthesis (FAS) pathway in primary chicken embryo fibroblasts (CEFs). In addition, MDV-infected cells contained high levels of fatty acids and showed increased numbers of lipid droplets (LDs). Chemical inhibitors of the FAS pathway (TOFA and C75) reduced MDV titers by approximately 30-fold. Addition of the downstream metabolites, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
(47 reference statements)
1
29
0
Order By: Relevance
“…Therefore, we believe that these cells are the only primary cells which are suited for analysis of MDV-induced cell metabolism. We had previously observed that 72 hpi is optimal timing for activation of both fatty acid synthesis and the COX-2/PGE2 pathway in MDVinfected cells (12). However, it should be emphasized that the results represent the metabolic alteration occurring in the infected cell culture, and we cannot exclude the possibility of bystander effects in which soluble factors released by the infected cells exert metabolic changes in noninfected bystander cells.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Therefore, we believe that these cells are the only primary cells which are suited for analysis of MDV-induced cell metabolism. We had previously observed that 72 hpi is optimal timing for activation of both fatty acid synthesis and the COX-2/PGE2 pathway in MDVinfected cells (12). However, it should be emphasized that the results represent the metabolic alteration occurring in the infected cell culture, and we cannot exclude the possibility of bystander effects in which soluble factors released by the infected cells exert metabolic changes in noninfected bystander cells.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, our results indicate that ATP production is increased in the MDV-infected cells via glycolysis and mitochondrial fatty acid ␤-oxidation in order to support virus replication. We had previously shown that MDV infection increases fatty acid synthesis (12); however, the role of fatty acid ␤-oxidation in MDV replication was unknown. Here, we demonstrate that fatty acid ␤-oxidation was not required for efficient replication of MDV, and the inhibition of ␤-oxidation by the CPT1a inhibitor, etomoxir, moderately increased virus titer, while it had no effect on viral copy numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support the third hypothesis. The knock-down of cyclooxygenase 2, an enzyme involved in inflammation, reduces MDV replication [ 36 ]. In addition, an enhancement of virus replication through inflammatory mediators was observed for the human cytomegalovirus, another herpesvirus, in human retinal pigment epithelial cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid analysis of the arterial smooth muscles in MDV-infected birds revealed a significant increase in nonesterified fatty acids, cholesterol, cholesterol esters, squalene, phospholipids, and triacylglycerol. Furthermore, excess lipid biosynthesis triggers the cellular deposition of lipid droplets in herpesvirus-infected cells ( Fabricant et al., 1981 ; Hajjar et al., 1986 ; Dai et al., 2017 ; Boodhoo et al., 2019 ). In MDV-infected primary chicken embryo fibroblasts, different lipid metabolites have different expression patterns, which may increase in fatty acid synthesis or breakdown of lipids or both ( Boodhoo et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%